To find the exponent that would make the two expressions equivalent, we can set the exponents equal to each other and solve for x.
(16^x)6 = (16^18)
Divide both sides of the equation by 6:
16^x = (16^18) / 6
Now, since the bases of both sides are the same (16), we can set the exponents equal to each other:
x = 18 / 6
Simplifying the right side of the equation:
x = 3
Therefore, the exponent that would make the two expressions equivalent is x = 3.
What exponent would make the two expressions equivalent: (16^x)6=(16^18)
1 answer